India, Uttar Pradesh : State Financial Accountability Assessment - World Bank (Washington, DC, 2013)
Uttar Pradesh (UP) is India's most populous State, and one of the poorest. Serious fiscal problems have emerged since the 1990s: the revenue deficit has increased significantly over the years, as well as the fiscal deficit, and, arrangements for accountability in the public sector have been undermined. Procedures exist for budgeting and monitoring the use of public resources, but there is little incentive to follow them. The Comptroller and Auditor General of India questions numerous departmental actions each year, but there is no compulsion on the executive branch to provide prompt answers, and to make necessary changes. Some useful progress has been made in implementing the financial management reform program over the last three years, as follows: 1) Computerization of the Treasuries in a network system has been completed at state government level, enabling the Government to monitor cash flows and prevent excess expenditures; 2) a Directorate of Internal Audit has been established in the Department of Finance to provide central leadership, and guidance in the development of departmental audit; and, 3) measures are being taken to establish better control over payrolls. The report reviews the strengths and weaknesses in financial management and accountability, to present a risk analysis that highlights widespread irregularities, and lack of prompt and predictable corrective action, meaning that the overall level of fiduciary risk remains high. It suggests there is significant scope for the Government of UP to improve the efficiency, and effectiveness of public spending through further consolidation of the budget, better matching of accountability with responsibility, routine enforcement of accountability, and greater transparency. This would be fully consistent with the fiscal reform program, and would have a direct impact on the GoUP's ability to provide more, and better quality public services to the poor. Recommendations suggest to a) depute one or more senior officials in the Finance Department to oversee public financial accountability reforms; b) review and update Financial Handbooks, Treasury Rules and Budget Manuals; c) develop and implement a Medium Term Expenditure framework in major spending departments of GoUP; and, d) strengthen accountability in Rural Local Bodies, in internal controls in Development Authorities, in internal audit within GoUP, in state government training institutions, and, build capacities within the Finance Department.